KAJIAN POTENSI DAN PENGEMBANGAN EKOWISATA BIRDWATCHING DI TAMAN NASIONAL MANUPEU TANAH DARU - , Benediktus Rio Wibawanto ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Manupeu Tanah Daru National Park located in Sumba Island, with an area of 87,984 ha, has a relatively high diversity of birds that can be used as the potential for birdwatching ecotourism development. Based on the research by using MacKinnon Listing Species Method, in all birdwatching track in Padiratana and Kambata Wundut, resulted 57 birds species that are divided in 32 families. Through scoring analysis of bird attraction for tourism, based on scarcity indicators, resulted 3 species of birds in very interesting category, there are Sumba hornbill (Rhyticeros everetti) and Sumba cockatoo (Cacatua sulphurea citrinocristata), Sumba boobook (Ninox rudolfi), 21 species in attractive and 33 species in low atrractive category. Determination of birdwatching track priority for ecotourism development through Neu Index Analysis, resulted second track in Kambata Wundut as a first priority, fourth track in Padiratana at second, first track in Sungai Bronjong Padiratana at third priority and third track in Kanabuwulang at last priority. Supported strengths such as the Sumba megalithic culture and easy accessibility, through SWOT analysis recommended aggressive strategies of birdwatching ecotourism development in Manupeu Tanah Daru National Park there are set Padiratana and Kambata Wundut area as collaborative birdwatching ecotourism model, community development, innovative birdwatching ecotourism products and marketing and promotion improvement.